Induction and growth of callus from agarwood hypocotyl (Aquilaria malaccensis Lam.) with additional 2,4-dichlorophenoxyacetic acid and kinetin - Fitriandi, Edi; Zakiah, Zulfa; Ifadatin, Siti (Buletin Kebun Raya, 2023)
Gaharu (Aquilaria malaccensis Lam.) is one of the non-timber forest product commodities producing secondary metabolites in the form of gaharu oil. It contains chromone compounds and contains resin or mastic which produces a fragrant smell, so it is used as a raw material for the cosmetic to the perfume industry. Conservation to multiply and produce gaharu secondary metabolites can be carried out using in vitro culture through callus culture. The study aimed to determine the effect of adding 2,4-D and kinetin to the Murashige Skoog medium on callus induction and growth of gaharu hypocotyls. The study used a completely randomized design (CRD) factorial with two treatment factors, namely 2,4-D concentrations (0, 0.022, 0.111, 0.221 mg/L) and kinetin concentrations (0, 0.022, 0.108, 0.215 mg/L). Parameters observed were callus appearance time (DST), percentage of explants forming callus (%), callus color and texture, wet weight and dry weight of callus (g). The results showed that all explants formed callus (100%), single 2,4-D treatment significantly affected callus appearance time from gaharu hypocotyl explants. The fastest mean time for callus appearance was shown in the addition of 0.221 mg/L 2,4-D without kinetin, which was 13.17 days after planting (DAP). The single 2,4-D treatment and the combination of 2,4-D and kinetin significantly affected the average callus dry weight. The highest average callus dry weight was in the combination treatment of 0.111 mg/L 2,4-D + 0.108 mg/L kinetin. The 2,4-D and kinetin treatments had no significant effect on the wet weight of the callus.